Distribution of visual attention within a cued area: evidence based on temporal order judgments - Mikael Cavallet (Psicologia: Reflexão e Crítica, 2011)
Three experiments were performed to investigate the distribution of attention across the visual field and the possibility of attentional resources to be more concentrated inside an abrupt onset frame (cue). The participants performed a temporal order judgment task of two letters presented in sequence; one letter presented inside and the other outside the frame. The results showed that the information presented inside the frame had its perceptual latency shortened in relation to the information presented outside the frame in experimental conditions where the frame orientation, the distance between the two letters and the cue onset time were manipulated. The advantage of the information presented inside the frame was attributed to the displacement of attention to the area delimited by the frame. The results contribute to the understanding of visual perception, showing that attentional resources may be redistributed inside the borders of a geometric figure.